2015
DOI: 10.1210/jc.2014-3885
|View full text |Cite|
|
Sign up to set email alerts
|

The Risk of Incident Type 2 Diabetes in a Korean Metabolically Healthy Obese Population: The Role of Systemic Inflammation

Abstract: MHO subjects show a substantially higher risk of incident type 2 diabetes than MHNO subjects. The level of systemic inflammation partially explains this increased risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 35 publications
7
80
0
1
Order By: Relevance
“…Compared to a European population, Americans had a higher prevalence of MHO, and this was consistent with a meta-analysis [42] focusing on the prevalence of MHO in adults. Studies in Korea showed that the prevalence of MHO varied from 5.7 to 25.8% and the prevalence of MUO from 13.6 to 25.9%, and most studies used ATPIII to define metabolic abnormality [22, 29, 43-45]. Our study revealed that the MHO prevalence was 4.2–11.4% and MUO prevalence was 12.9–20.1% when we adopted ATPIII, CDS, Wildman, and Karelis criteria to define metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to a European population, Americans had a higher prevalence of MHO, and this was consistent with a meta-analysis [42] focusing on the prevalence of MHO in adults. Studies in Korea showed that the prevalence of MHO varied from 5.7 to 25.8% and the prevalence of MUO from 13.6 to 25.9%, and most studies used ATPIII to define metabolic abnormality [22, 29, 43-45]. Our study revealed that the MHO prevalence was 4.2–11.4% and MUO prevalence was 12.9–20.1% when we adopted ATPIII, CDS, Wildman, and Karelis criteria to define metabolic status.…”
Section: Discussionmentioning
confidence: 99%
“…6 In brief, the study subjects were recruited from among those aged 420 years who visited the Health Screening and Promotion Center of Asan Medical Center (Seoul, Republic of Korea) between March 2007 and December 2013 for routine medical examinations. During this period, a total of 151,759 subjects participated in this examination.…”
Section: Materials and Methods Study Populationmentioning
confidence: 99%
“…Drinking habits were categorized as frequency per week (that is, ⩽ 1 time/week and ⩾ 2 times/week (moderate drinker)); smoking habits were categorized as noncurrent or current; and exercise habits were categorized as frequency per week (that is, ⩽ 2 times/week and ⩾ 3 times/week (physically active)). 6,51 History of cardiovascular disease was based on each subject's history of angina, myocardial infarction, and/or cerebrovascular accidents, all of which were diagnosed by a physician. Subjects with diabetes were defined as those with a FPG level ⩾ 7.0 mmol/l and/or hemoglobin A1c level ⩾ 6.5%.…”
Section: Kidney Internationalmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude and consistency of excess risk for type 2 diabetes among healthy obese adults fits with what is known about progressions from healthy to unhealthy obesity, given strong links with future insulin resistance (57) which subsequently induces hyperglycaemia. Since this meta-analysis, at least 6 additional studies have examined type 2 diabetes risk among healthy obese versus healthy normal-weight adults, all of which report excess risk of a similar magnitude (65)(66)(67)(68)(69)(70).…”
Section: Is Healthy Obesity Harmless?mentioning
confidence: 99%